Harmonic Analysis on Torque Ripple of Brushless DC Motor Based on Advanced Commutation Control - Yanpeng Ji; Bin Li; Jingcheng Sun (Journal of Control Science and Engineering)
This paper investigates the relationship between current, back electromotive force (back-EMF), and torque for permanent-magnet brushless DC (PM BLDC) motors under advanced commutation control from the perspective of harmonics. Considering that the phase current is the influencing factor of both torque and torque ripple, this paper firstly analyzes the effects of advanced commutation on phase current and current harmonics. And then, based on the harmonics of the phase current and back-EMF, the torque harmonic expressions are deduced. The expressions reveal the relationship of harmonic order between the torque, phase current, and back-EMF and highlight the different contribution of individual torque harmonic to the total torque ripple. Finally, the proposed harmonic analysis method is verified by the experiments with different speed and load conditions.